Genomic Analysis Identifies Mutations Concerning Drug-Resistance and Beijing Genotype in Multidrug-Resistant Mycobacterium tuberculosis Isolated From China - Wan, Li; Liu, Haican; Li, Machao; Jiang, Yi; Zhao, Xiuqin; Liu, Zhiguang; Wan, Kanglin; Li, Guilian; Guan, Cha-xiang (Frontiers in Microbiology, 2020)
Development of modern genomics provides us an effective method to understand the molecular mechanism of drug resistance and diagnose drug-resistant Mycobacterium tuberculosis. In this study, mutations in 18 genes or intergenic regions acquired by whole-genome sequencing (WGS) of 183 clinical M. tuberculosis strains including 137 multidrug resistant and 46 pan-susceptible isolates from China were identified and used to analyze their associations with resistance of isoniazid, rifampin, ethambutol and streptomycin. Used proportional method as the gold standard method, the accuracy values of WGS to predict resistance were calculated. The association between synonymous or lineage definition mutations with different genotypes were also analyzed. The results showed that compared to phenotypic proportional method, the sensitivity and specificity of WGS for resistance detection were 94.2% and 100.0% for rifampicin (based on mutations in rpoB), 90.5% and 97.8% for isoniazid (katG), 83.0% and 97.8% for streptomycin (rpsL combined with rrs 530 loop and 912 loop), 90.9% and 65.1% for ethambutol (embB), respectively. WGS data also showed that mutations in the inhA promoter increased only 2.2% sensitivity for INH based on mutations in katG. Synonymous mutation rpoB A1075A was confirmed to be associated with Beijing genotype. This study confirmed that mutations in rpoB, katG, rrs 530 loop and 912 loop and rpsL were excellent biomarkers for predicting rifampicin, isoniazid, and streptomycin resistance, respectively and provided clues in clarifying the drug resistance mechanism of M. tuberculosis isolates from China.